2017
DOI: 10.1175/jtech-d-16-0160.1
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale Eddies in the Taiwan Strait Observed by High-Frequency Radars: Detection Algorithms and Eddy Properties

Abstract: This study compared the efficiencies of two widely used automatic eddy detection algorithms—that is, the winding-angle (WA) method and the vector geometry (VG) method—and investigated the submesoscale eddy properties using surface current observations derived from high-frequency radars (HFRs) in the Taiwan Strait. The results showed that the WA method using the streamline and the VG method based on the streamfunction field have almost the same capacity for identifying eddies, but the former is more competent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Although technological advances have resulted in increases in the density of sampling rates over time and space and the development of the Lagrangian sampling strategy, which involves following and crossing the target phenomena, these observations have mainly focused on specific submesoscale events and phenomena and are available for a limited number of realizations (e.g., Baschek & Molemaker, ; Callies et al., ; D'Asaro et al., ). In contrast, operational and concurrent Eulerian observations using remote sensing instruments can thoroughly investigate submesoscale processes via statistical analyses using available data such as high‐frequency radar (HFR)‐derived surface currents (e.g., Kim et al., ; Kirincich, ; Lai et al., ) and geostationary ocean color imagery (GOCI)‐derived surface concentration maps of chlorophyll, total suspended solids, and colored dissolved organic matter (e.g., Choi et al., ), which are available at hourly and kilometer‐scale resolutions and are abundant relative to classic in situ measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Although technological advances have resulted in increases in the density of sampling rates over time and space and the development of the Lagrangian sampling strategy, which involves following and crossing the target phenomena, these observations have mainly focused on specific submesoscale events and phenomena and are available for a limited number of realizations (e.g., Baschek & Molemaker, ; Callies et al., ; D'Asaro et al., ). In contrast, operational and concurrent Eulerian observations using remote sensing instruments can thoroughly investigate submesoscale processes via statistical analyses using available data such as high‐frequency radar (HFR)‐derived surface currents (e.g., Kim et al., ; Kirincich, ; Lai et al., ) and geostationary ocean color imagery (GOCI)‐derived surface concentration maps of chlorophyll, total suspended solids, and colored dissolved organic matter (e.g., Choi et al., ), which are available at hourly and kilometer‐scale resolutions and are abundant relative to classic in situ measurements.…”
Section: Introductionmentioning
confidence: 99%
“…This method is suitable for measuring the velocity field. It has been successfully applied to different study regions, such as the leeward side of Hawaii [42], the subtropical zonal band of the North Pacific Ocean [43], the Taiwan Strait [18], and the Kuroshio Extension Region [44]. We invite the reader to refer to Nencioli et al [33] for more details.…”
Section: Eddy Detection Algorithmmentioning
confidence: 99%
“…However, in recent years, high-precision observations have mainly focused on some special submesoscale events and phenomena, due to increased sampling rates in time and space [6,11]. Remote-sensing observations can also be used to investigate SPs, such as surface currents derived by high-frequency radar [2,[17][18][19], geostationary ocean color imagery (GOCI)-derived chlorophyll surface concentration maps, and colored dissolved organic matter [20], which are available at hourly and kilometer-scale resolutions. HFRs can provide information on ocean surface currents over a large, horizontal distance with high spatial-temporal resolution, which can reach up to 200 m in space (e.g., SeaSonde [21]) and 20 min in time.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of HFR surface current measurements have validated the capacity of the direction-finding HFR to remote sensing the ocean surface currents through comparisons with in situ current measurements, such as [8][9][10][11][12]. These studies demonstrated that there is a 7-20 cm/s differences between the current measurements derived from the directionfinding HFRs and those from the in situ instrument.…”
Section: Introductionmentioning
confidence: 97%